2000
DOI: 10.1007/s001270050199
|View full text |Cite
|
Sign up to set email alerts
|

The geographical mobility of severely mentally ill residents in London

Abstract: Geographical mobility of psychiatric patients in London is high and is particularly marked for those presenting for in-patient treatment. These findings suggest that greater mobility could be one of the most important reasons for the higher than expected demands on psychiatric services and the difficulties in maintaining contact with patients in London in general and inner London in particular. More attention should be paid to geographical mobility as a predictor of psychiatric service use, and it is recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…This has been primarily characterised by linking interests in place (geography and setting) and relating this to spatial health service issues of need, access and provision. The work of Giggs and Cooper (1987) focused on the relationship between the clustering of mental ill-health in city centre areas and how this might have an explanation associated with proximity to services, while issues of mobility also arose in the work of Lamont, Ukoumunne, Tyrer, Thornicroft and Slaughter (2000). Dear and Wolch (1997) focused on the impacts of de-institutionalisation of mental health provision on local geographies of mental health in cities, a pattern common to many western societies.…”
Section: Health Geographiesmentioning
confidence: 99%
“…This has been primarily characterised by linking interests in place (geography and setting) and relating this to spatial health service issues of need, access and provision. The work of Giggs and Cooper (1987) focused on the relationship between the clustering of mental ill-health in city centre areas and how this might have an explanation associated with proximity to services, while issues of mobility also arose in the work of Lamont, Ukoumunne, Tyrer, Thornicroft and Slaughter (2000). Dear and Wolch (1997) focused on the impacts of de-institutionalisation of mental health provision on local geographies of mental health in cities, a pattern common to many western societies.…”
Section: Health Geographiesmentioning
confidence: 99%
“…There is a strong body of evidence that suggests residential mobility is more common among psychiatric patients and the mentally ill than with the general population. [41][42][43][44] This evidence suggests that we may be underestimating the return visit rates of the self-inflicted injury group. Although it may be more likely that individuals in the self-inflicted injury group relocated outside of the city, we cannot verify this in the current study.…”
Section: Limitationsmentioning
confidence: 99%
“…Inter-region migration, including rural-to-urban migration, may account for geographic concentrations of individuals who require specialized health care services. Previous research has found, for example, that individuals with mental illness tend to move into areas where they have previously obtained health care services (Breslow, Klinger, & Erickson, 1998;Lamont et al, 2000). Health service planners can use data on mobility in order to ensure a good match between population needs and the provision of services.…”
mentioning
confidence: 97%
“…This is particularly evident in studies of the residential mobility of individuals with SMI. Data are primarily obtained from the case registries of specific facilities or service providers (e.g., Abood et al, 2002;Chesteen et al, 1970;Lamont et al, 2000); this limits the generalizability of study findings to the larger population of individuals diagnosed with SMI. Moreover, population-based data have rarely been used to select comparison groups that are representative of either the general population or of populations with different types of health conditions (e.g., Lesage & Tansella, 1989).…”
mentioning
confidence: 99%